Advanced voltage regulation method of power distribution systems interconnected with dispersed storage and generation systems. - Joon-Ho Choi
This paper deals with an issue of voltage regulation for power distribution systems interconnected with dispersed storage and generation (DSG) systems. Since DSGs within power distribution systems impact on the conventional voltage regulation method, there is a possibility that customers' voltages violate the permissible limits. A multiple line drop compensation (MLDC) voltage regulation method that determines tap positions of under-load tap changer (ULTC) transformers is proposed to maintain the customers' voltages within the permissible limits. Several case studies indicate that the proposed MLDC voltage regulation method can be applied well to practical power distribution systems having DSGs and/or severely unbalanced load diversity on different feeders
Keywords: Advanced voltage regulation method; Case studies; Control design; Control simulation; Dispersed storage and generation; Interconnected power systems; Multiple line drop compensation; Power distribution systems; Unbalanced load diversity; Under-load tap changer transformers